Предмет:
Другие предметыАвтор:
анонимСократим дроби:
а) (a² - 4)/(2 * a - a²) = (a - 2) * (a + 2)/(a * (2 - a)) = -(a - 2) * (a + 2)/(a * (a - 2)) = -1 * (a + 2)/(a * 1) = -(a + 2)/a;
б) (3 * x - 3 * c)/(a * c - a * x) = 3 * (x - c)/(a * (c - x)) = -3 * (x - c)/(a * (x - c)) = -3/a;
в) (x³ - x)/(x - x²) = x * (x² - 1)/(x * (1 - x)) = (x² - 1)/(1 - x) = (x - 1) * (x + 1)/(1 - x) = -(x - 1) * (x + 1)/(x - 1) = -(x + 1) = -x - 1;
г) (a² * x - a * x²)/(x² - a * x) = a * x * (a - x)/(x * (x - a)) = a * (a - x)/(x - a) = -a * (a - x)/(a - x) = -a.
Автор:
headlightsxin9Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть